Impact of Obesity on Respiratory Health: The Role of Sport and Physical Activity in Prevention and Management - Makuch, Rafał; Kucharski, Adam; Pilarski, Konrad; Chrościcka , Alicja; Gała, Kamil; Czajka, Andrzej; Lenard, Paweł; Michalska, Sara; Dewicka, Martyna; Wawrzyniak, Alicja Maria (Quality in Sport, 2024)
Introduction and Objective: Obesity is a major social and economic problem. Since the 1980s, the number of overweight and obese people has doubled. Treatment of such patients is 30% more expensive than for people of normal weight. The main aim of the article is to present the impact of the occurrence of respiratory diseases and the deterioration of the system function. In addition, the article reviews the impact of physical activity and diet on weight loss and the prevention of further weight gain. Review and Methods: Review and summary of studies and meta-analysis of studies available in open-source format on Google Scholar and PubMed. Abbreviated Description of the State of Knowledge: One of the most common diseases in the population is bronchial asthma. People with excess body weight have a more severe course, and numerous studies have been carried out to explain the cause. The main mechanism that worsens respiratory function is mechanical compression by fatty tissue. It has also been observed that the inflammatory response, underlying the etiopathogenesis of asthma, may be caused by the secretion of inflammatory mediators by adipocytes. This is currently being investigated. Obstructive sleep apnea is a disorder that results in a fragmentation of sleep, which has serious health consequences and leads to a reduction in quality of life. Obesity is a major risk factor. The severity of the condition is strongly related to excess body weight. Obese hypoventilation syndrome is a condition in which obesity impairs alveolar ventilation and CO2 removal, resulting in hypercapnia, which can lead to respiratory failure. Summary: Weight loss and interventions to prevent weight gain in people with a baseline BMI >25 kg/m2 are fundamental to good health. For best results, a calorie-restricted diet should be combined with physical activity. The WHO has created recommendations for the amount of physical activity needed each week.